2005
DOI: 10.1159/000084775
|View full text |Cite
|
Sign up to set email alerts
|

The Educational Needs and Professional Roles of Canadian Physicians and Nurses regarding Genetic Testing and Adult Onset Hereditary Disease

Abstract: Objective: To investigate the knowledge, professional involvement and confidence of Canadian nurses and physicians in providing genetic services for adult onset hereditary disease. Methods: 1,425 physicians and 1,425 nurses received a mailed questionnaire with reminders. The response rates were 50% (n = 543) and 79% (n = 975), respectively. Results: Forty-eight percent of physicians and 31% of nurses lacked formal education in genetics. Respondents reported being involved in caring for people at risk for adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 20 publications
4
65
0
2
Order By: Relevance
“…In the study reported in this review by Bottorff et al [35] it is clear that nurses' knowledge of genetics was much less satisfactory than that of physicians in the study. This may not be surprising since the analysis indicated that the majority of respondents to the reviews studies had not received formal education in genetics.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In the study reported in this review by Bottorff et al [35] it is clear that nurses' knowledge of genetics was much less satisfactory than that of physicians in the study. This may not be surprising since the analysis indicated that the majority of respondents to the reviews studies had not received formal education in genetics.…”
Section: Discussionmentioning
confidence: 62%
“…In Bottorff et al's [35] study, nearly half of the nurses and almost a third of the physicians reported receiving no formal education in genetics. Only 7% of the nurses reported completing semester courses in genetics.…”
Section: Genetics Educationmentioning
confidence: 98%
See 1 more Smart Citation
“…In its 2003 White Paper on genetics, the UK Department of Health emphasized that education for health professionals is vital if advances in genetics are to be translated effectively into everyday practice (Waters 2004). Therefore, the development of educational programs for nursing knowledge and counseling as well as basic curricula in genetic nursing at universities are essential for the near future (Kim 2003;Bottorff et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the survey found a positive correlation between the nurses' level of knowledge and their degree of interest in genetics. Bottorff et al [20] studied the educational needs and professional roles of Canadian physicians and nurses, and they reported that 48% of physicians and 31%…”
Section: Discussionmentioning
confidence: 99%